FHOD‐1 is the only formin in Caenorhabditis elegans that promotes striated muscle growth and Z‐line organization in a cell autonomous manner. Issue 10 (6th November 2020) - Sundaramurthy, Sumana; Votra, SarahBeth; Laszlo, Arianna; Davies, Tim; Pruyne, David
Abstract: The striated body wall muscles of Caenorhabditis elegans are a simple model for sarcomere assembly. Previously, we observed deletion mutants for two formin genes, fhod‐1 and cyk‐1, develop thin muscles with abnormal dense bodies (the sarcomere Z‐line analogs). However, this work left in question whether these formins work in a muscle cell autonomous manner, particularly since cyk‐1(∆) deletion has pleiotropic effects on development. Using a fast acting temperature‐sensitive cyk‐1(ts) mutant, we show here that neither postembryonic loss nor acute loss of CYK‐1 during embryonic sarcomerogenesis cause lasting muscle defects. Furthermore, mosaic expression of CYK‐1 in cyk‐1(∆) mutants is unable to rescue muscle defects in a cell autonomous manner, suggesting muscle phenotypes caused by cyk‐1 (∆) are likely indirect. Conversely, mosaic expression of FHOD‐1 in fhod‐1(Δ) mutants promotes muscle cell growth and proper dense body organization in a muscle cell autonomous manner. As we observe no effect of loss of any other formin on muscle development, we conclude FHOD‐1 is the only worm formin that directly promotes striated muscle development, and the effects on formin loss in C . elegans are surprisingly modest compared to other systems.